THE ERROR ANALYSIS OF DERIVATIONAL MORPHOLOGY IN EFL ENGLISH NARRATIVE COMPOSITIONS - Kusumawardhani, Paramita (Universitas Negeri Makassar, 2018)
Derivational morphology in the learners’ English narrative compositions was the main purpose of this research. Morphology is the study of morphemes which are the smallest significant units of grammar. There are two kinds of morphology: derivational and inflectional morphology. Derivational morphology is related to affixes such as suffixes, infixes, prefixes, ablaut and reduplication, meanwhile inflectional morphology is related to plural, possessive, past time, progressive, and comparative and superlative. Morphology mostly used in writing and it is one of the difficult parts in English subject. There are four kinds of composition: argumentation, description, exposition and narration. The data was taken from the students of grade XI of a Public High School in Tangerang. Descriptive method was used in this paper. There is some derivational morphology found in this research: derivation of a noun, adverb, gerund after a preposition, gerund after the verb, to-infinitive, present participle, passive participle, modals, and adjective.